Influence of Probiotics and Acidifier supplementation on Growth, Carcass Characteristics and Economics of Feeding in Broilers - Rout, S. K.; Pradhan, C. R.; Rath, Rajashree; Panda, N.; Panigrahi, B.; Pati, P. K. (Indian Journal of Animal Nutrition, 2018)
One hundred and fifty, day-old Vencobb broiler chicks of either sex with uniform body weight were randomly assigned to four treatments of three replicates each having 10 birds. The chicks in all the groups were fed with starter ration up to 21 days and finisher ration from 22 to 42 days of age as per BIS (1992) recommendations, however, in treatments T2, T3 and T4, the chicks were also provided with probiotics @ 50 g,acidifier @ 2 kg and probiotics @ 50 g + acidifier @ 2 kg/tonne of feed, respectively. The basal diet served as treatment T1. Body weight gain was higher (P<0.05) in group T4 compared to groups T3 or T2 in all the weeks. FCR at 6th week was better (P<0.05) in group T4 compared to the control with no significant difference between the supplemented groups. Net return per kg live weight gain was the highest for group T4 followed by T3, T2 and control group, however, the differences among the groups were not significant. The carcass characteristics were similar in all the groups. It was concluded that probiotics and acidifiers supplementation either singly or in combination improved the growth performance and feed efficiency in commercial broilers, however, the combination of probiotics and acidifier gave the best results.